Advanced Treatment: Tackling Paracetamol with Fenton Oxidation and Membrane Hybrid Processes - Fadhila Malahayati Kamal; Sucipta Laksono; Sandyanto Adityosulindro (Journal of the Civil Engineering Forum, 2024)
Paracetamol (PCT) in aquatic environments has become a global concern due to its potential harm to humans and environments. However, conventional water treatment was only able to degrade PCT partially. It was necessary to treat PCT contaminated water with tertiary technologies in particular by combination approach, such as Fenton oxidation and membrane filtration process. This combined approach enabling mitigation of large chemical footprint and iron residue associated with Fenton oxidation, as well as reducing fouling tendency of the membrane. The aim of this study was to evaluate the PCT removal efficiency by hybrid technology Fenton oxidation and membrane filtration. The membrane performance during the filtration process was also analyzed. As an important parameter for Fenton process, concentration of H 2 O 2 /Fe 2+ with ratio of 1:0.5 resulted in optimal removal of 45% PCT in terms of COD removal. However, separation using flat sheet Polyethersulfone Ultrafiltration (UF) with constant flux of 120 L/m²·h resulted in insignificant of COD removal. Nevertheless, the UF process was able to remove up to 54% of Fe 2+ at pH in alkaline condition with 8.5. In addition, a decrease in membrane permeability down to 0.2 L/m²h/bar over time, according to the filtered specific volume during the UF process, indicates fouling of the UF membrane during the 120 minutes of filtration. While the combined approach does not show significant improvement in COD removal, it does help to reduce the chemical footprint of the process, which is an important factor for the applicability of the selected water treatment method.